Assessment of Water Quality Index and Pollution Load Capacity in the Sukowidi River and Bendo River, Banyuwangi Region - Arief Rachmansyah; Akhmad Adi Sulianto; Novia Lusiana; Luhur Akbar Devianto (Indonesian Journal of Environment and Sustainable Development, 2021)
The river is a part of the surface water resource which is very potential for living. The quality of river water is greatly influenced by land use and human activities in the catchment area. Increasing the number population in Banyuwangi Region and its activity has the potential to reduce the water quality of the river, especially in the Sukowidi and Bendo catchment area, therefore it is necessary to assess the water quality. This research was conducted to identify the source of pollutants and determine the pollution index, status of water pollution, as well as to determine pollution load capacity. The data analysis was carried out quantitatively and graphically, and spatially with the QUAL2Kw and the Inverse Distance Weighted (IDW) by usingÂ  ArcGIS 10.4.1. Land use on the two rivers is slightly different, that is rural, suburban, and urban areas. The pollution sources in the study area were point source and non-point source. The results showed that the pollution status of the Sukowidi River was "Light Polluted" and the high pollutant load carrying capacity had total suspended solids and nitrates. Meanwhile, in the Bendo River, the pollution status is not polluted yet and the pollutant load carrying capacity is on the quality standards. These findings provide valuable information and guidance for the Banyuwangi Regency government to decide on land use policy.